Ordering Goods Application Design Using Macros Visual Basic Applications (JESII: Journal of Elektronik Sistem InformasI, 2023)
PT M Indonesia is one of the big companies in the world, as one of the companies engaged in the manufacture of toys PT M Indonesia does not close itself to the technology of industrial development 4.0. PT M really prioritizes technology that might be able to sophisticate, speed up, or make it easier for employees to work. For example, the author has conducted research, namely making an application for ordering goods using Microsoft Excel macro visual basic applications. The purpose of this research is to order goods online without using paper. The application of ordering goods using macro visual basics application is made using the research method used by the author in conducting this research is the waterfall method. The research that the author has done, is expected to speed up the approval process and the spread of the virus which is carried out by ordering goods manually using paper to be online via email. Using visual basic macros from Microsoft Excel because employees are more familiar with using Microsoft Excel macros so that employees can easily manage data also Microsoft Excel macros make it easier to enter order data into the system or database from PT M Indonesia.